In vivo keratotomy by mid-infrared femtosecond laser resonant with amide vibrational mode - Jinmiao Guo; Pengfan Chen; Maoxing Xiang; Kan Tian; Zhongjun Wan; Linzhen He; Wenkai Li; Xu Peng; Yujie Peng; Xiangyi Wen; Longqian Liu; Qi Jie Wang; et al. (Communications Medicine)
Abstract Background Laser keratotomy, a corneal incision technique for vision correction, has advanced with near-infrared (NIR) femtosecond (fs) lasers-ultrashort pulsed light sources in the near-infrared spectrum. However, NIR femtosecond lasers encounter challenges such as postoperative astigmatism due to scattering by edematous tissues, and endothelial cells distortion by mechanical impact. Methods The mid-infrared (MIR) femtosecond lasers at a central wavelength of 6.1 μm resonating with amide modes has an output power of 100 mW and a pulse width of ~200 fs. Systematic experiments of MIR fs laser keratotomy are performed on corneas of 8-week-old male C57BL/6J mice, with optical coherence tomography and fluorescein staining for evaluating corneal recovery in vivo. Electroretinography and visual cliff test are performed for evaluating potential adverse effects on retinal and visual function. Immunofluorescence and immunohistochemistry are carried out for accessing the density, morphology and function of endothelial cell, and the structure of incision and recovery condition of cornea after sacrificing the mice. Results Efficient deep keratotomy with minimal collateral damage is realized both in normal and edematous cornea, surpassing traditional NIR femtosecond lasers by experimental comparison. Histological imaging, fluorescein staining and immunofluorescence reveal that corneal incisions ablated by MIR fs laser can heal within 3 days by identifying optimal ablation parameters. Additionally, through the electrophysiology and visual cliff index evaluations, it is confirmed that no postoperative retinal and visual impairment caused, proving a good biological safety. Conclusions Keratotomy by MIR fs laser exhibits favorable ablative efficiency and biosafety in mice, which could serve as a new tool for ophthalmic surgery and extend the applications of femtosecond laser assisted keratotomy.